Application of Business Intelligence in Enterprise Systems to Support Strategic Decision Making - Abrar Hiswara (West Science Information System and Technology, 2025)
This study investigates the application of Business Intelligence (BI) in corporate systems and its role in supporting strategic decision making in Indonesian companies. Using a quantitative research approach, data were collected from 75 corporate employees who actively use BI-based systems and are involved in managerial or strategic roles. The research instrument employed a Likert scale to measure perceptions of BI application and strategic decision-making effectiveness. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) version 25, including descriptive statistics, validity and reliability tests, and regression analysis. The results indicate that Business Intelligence application has a positive and significant effect on strategic decision making, with BI explaining 45% of the variance in decision-making effectiveness. Key aspects such as data quality, analytical capability, and system usability were found to play a crucial role in enhancing decision quality, timeliness, and managerial confidence. The findings provide empirical evidence that Business Intelligence functions as a strategic resource that supports data-driven management and improves organizational competitiveness in the Indonesian corporate context.